Image defogging algorithm based on guided filtering and adaptive tolerance - Xianli JIN; Wei ZHANG; Linfeng LIU (Tongxin xuebao)
Aiming at the problem of distortion of dark channel algorithm in defogging the sky region,an improved image defogging algorithm based on the guided filtering and adaptive tolerance mechanism was proposed.Firstly,the fitted transmissivity graphs were calculated for the windows with different sizes.Then,the transmissivity was further refined by the guided filtering technique.After that,the transmissivity in sky area was revised by an adaptive tolerance mechanism.Finally,the restored image was converted from RGB space to HSV space,and thus the brightness and contrast of the images could be color compensated.Experimental results show that the proposed algorithm restores the images effectively and obtain preferable defogging results with regard to the processing of bright areas such as the sky areas.